Purchase Atlassian Licenses [Tender documents : T490970317] (MENA Report, 2023)
Contract notice: purchase atlassian licenses In view of the character limit, the full definition of the subject of the procedure is recorded in this section: acquisition of atlassian or equivalent licenses for the purpose of supporting internal processes, according to the technical description.Idomsoft zrt. to perform its public duties, it is necessary to obtain atlassian or equivalent licenses as follows: 1 pc. - jira software (data center) 1000 users: commercial term license / 1 year 1 pc - configuration manager for jira (cmj) data center for jira software (data center) 1000 users: commercial term license 1 pc - dynamic forms for jira data center for jira software (data center) 1000 users: commercial term license1 pc - email this issue data center for jira software (data center) 1000 users: commercial term license1 pc. - extension for jira service management data center for jira software (data center) 1000 users: commercial term license 1 pc. - jira misc workflow extensions (jmwe) data center for jira software (data center) 1000 users: commercial term license 1 pc. - jsu automation suite for jira workflows data center for jira software (data center) 1000 users: commercial term license 1 pc. - scrum poker for jira data center for jira software (data center) 1000 users: commercial term license 1 pc. - table grid editor data center for jira software (data center) 1000 users: commercial term license 1 pc. - table grid next generation data center for jira software (data center) 1000 users: commercial term license 1 pc. - timesheets by tempo - jira time tracking (data center) 1000 users: commercial term license 1 pc. - xporter - export issues from jira data center for jira software (data center) 1000 users: commercial term license 1 pc. - confluence (data center) 1000 users: commercial term license / 1 year 1 pc. - excellent spreadsheet for confluence data center for confluence (data center) 1000 users: commercial term license 1 pc. - inline comments in the editor data center for confluence (data center) 1000 users: commercial term license 1 pc. - numbered headings data center for confluence (data center) 1000 users: commercial term license 1 pc. - scriptrunner for confluence data center for confluence (data center) 1000 users: commercial term license 1 pc. - table filter and charts for confluence data center for confluence (data center) 1000 users: commercial term license 1 pc. - bitbucket (data center) 500 users: commercial term license / 1 year 1 pc. - awesome graphs for bitbucket data center for bitbucket (data center) 500 users: commercial term license 1 pc. - include code quality for bitbucket data center for bitbucket (data center) 500 users: commercial term license renewalsupport entitlement1 pc. - bamboo (data center) 10 remote agents: commercial license / 1 year 1 pc - include code quality for bamboo (data center) 10 remote agents: commercial license renewalsupport entitlement the detailed description of the subject of procurement is inclu Major organization : IDOMSOFT INFORMATIKAI ZRTKRUEN MUKDO RSZVNYTRSASG Address : Vci t 133 Country :Hungary Email : beszerzes@idomsoft.hu Url : http://www.idomsoft.hu Tender notice number : 407116-2023 Notice type : T490970317.html © 2022 Al Bawaba (Albawaba.com) Provided by SyndiGate Media Inc. (Syndigate.info).